EVALUASI PERANAN LEASING SEBAGAI ALTERNATIF PEMBIAYAAN MODAL PADA PT JOKOTOLE TRANSPORT SURABAYA - Simatupang, Nurhamida (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2014)
In this research there are two types of sources of capital goods financing which can be used by the company to gain their fixed assets that is through leasing and bank credit. The problem in this research is which alternative is more profitable between leasing and bank credit. The type of research which is used by the researcher to solve the problem is descriptive research which is carried out by using case study and qualitative approach. The data collection technique has been carried out by performing observation, documentation, interview, and by conducting financing comparative analysis between leasing and bank credit. The result of the research shows that leasing with option rights (financial lease) is the financing alternative which is more profitable than bank credit alternative, since the tax savings which has been gained by the company through leasing alternative is bigger than bank credit alternative, and from the service aspect, through leasing, the company is easier to gain fixed asset without undergoing complicated procedure. In the end, this research can give the result as the original purpose of this research. Therefore, the result of this research can be used as the reference for the company in making decision.Keywords: Capital Savings, Leasing with Option Rights, Bank Credit